Peak particlevelocitydataacquisitionfor monitoring blast induced earth quakes in quarry sites (2018)
The peak particle velocity datasets recorded during quarry blasts in the neighborhood villages and towns in Ibadan and Abeokuta were processed and analyzed in order to recommend a safe blast design for each of the quarries. The minimum peak particle velo- city of 48.27 mm/s was recorded near the foundation of the nearest residence at the shot to monitored distance of 500m. The ten- dency of ground vibration emanating from the quarry sites to cause damage to the structures in the nearby dwelling areas is very high. The peak particle velocity datasets recorded were not within the safe limit. Therefore, the peak particle velocity that will not exceed 35 mm/s is recommended for a safe blast design